Preventing acute kidney injury in high-risk patients by temporarily discontinuing medication – an observational study in general practice - Suzanne J. Faber; Nynke D. Scherpbier; Hans J. G. Peters; Annemarie A. Uijen (BMC Nephrology, 2019)
Abstract Background Elderly, patients with chronic kidney disease (CKD) and patients with heart failure who continue using renin-angiotensin-aldosterone-system (RAAS) inhibitors, diuretics, or non-steroidal-anti-inflammatory drugs (NSAIDs) during times of fluid loss have a high risk of developing complications like acute kidney injury (AKI). The aim of this study was to assess how often advice to discontinue high-risk medication was offered to high-risk patients consulting the general practitioner (GP) with increased fluid loss. Furthermore, we assessed the number and nature of the complications that occurred after GP consultation. Methods We performed a cross-sectional study with patients from seven Dutch general practices participating in the Family Medicine Network between 1 and 6-2013 and 1-7-2018. We included patients who used RAAS-inhibitors, diuretics, or NSAIDs, and had at least one of the following risk factors: age ≥ 70 years, CKD, or heart failure. From this population, we selected patients with a ‘dehydration-risk’ episode (vomiting, diarrhoea, fever, chills, or gastrointestinal infection). We manually checked their electronic patient files and assessed the percentage of episodes in which advice to discontinue the high-risk medication was offered and whether a complication occurred in 3 months after the ‘dehydration-risk’ episode. Results We included 3607 high-risk patients from a total of 44.675 patients (8.1%). We found that patients were advised to discontinue the high-risk medication in 38 (4.6%) of 816 ‘dehydration-risk’ episodes. In 59 of 816 episodes (7.1%) complications (mainly AKI) occurred. Conclusions Dutch GPs do not frequently advise high-risk patients to discontinue high-risk medication during ‘dehydration-risk’ episodes. Complications occur frequently. Timely discontinuation of high-risk medication needs attention.